Substitusi Silase Secara Kimiawi Limbah Padat Surimi Ikan Swanggi (Priacanthus macracanthus) pada Tepung Ikan terhadap Retensi Energi dan Rasio Konversi Pakan Benih Ikan Nila (Oreochromis niloticus) [Chemical Silage Substitution of Swanggi Surimi Solid Waste (Priacanthus macracanthus) of Fish Meal Toward Energy Retention and Tiplapia Seeds (Oreochromis niloticus) Feed Conversion Rate] - Boedi Setya Rahardja; Prayogo Prayogo; Wiku Bakti Bawono (Faculty of Fisheries and Marine Universitas Airlangga, 2015)
Abstract Swanggi surimi waste can be processed into economically valuable source of protein through chemical treatment processes produce crude protein content ranging from 51%. Results of high energy retention and reduced feed conversion ratio of solid waste as a substitute swanggi fish surimi fish meal is expected to optimize the growth of tilapia with lower feed prices, thereby reducing the high cost of feed in aquaculture. This study aims to determine the chemical silage substitution of solid waste swanggi fish surimi (P. macracanthus) in fish meal. The experimental design completely randomized design (CRD) with four treatments with five replications. The treatment used is the number of different proteins in each feed rations. The main parameters are observed energy retention (%) and feed conversion ratio. Analysis of data using analysis of variance (ANOVA) and followed Duncan's multiple range test. These results indicate that substitution is chemically silage solid waste swanggi surimi fish in fish meal provides highly significant effect (p <0.05) on the retention of energy and feed conversion ratio tilapia fish. The average retention of the highest energy on a few observations are in treatment P3 (67,90a ± 0.86%) and the lowest at P0 (64,72b ± 1.17%). Average feed conversion ratio was lowest for the treatment P3 (2,41c ± 0.028) and the highest pda P0 (2,50a ± 0.018).